Taste perception as a risk factor for childhood obesity - Ana Carolina Ariza; Tania G Sánchez-Pimienta; Juan A Rivera (Instituto Nacional de Salud Pública, 2018)
Objective. To describe the role of taste perception in the development of sweet taste habituation as well as its relationship to the development of obesity in children. Materials and methods. An initial search of scientific articles published in PubMed between January 1st, 2011 and March 20th, 2016 was performed in children between 0 and 12 years old. The algorithms used were (Obesity OR Overweight) AND(Taste perception, Satiation, Satiety response, Appetite, Appetite regulation Habituation, Taste receptors [MeSH]) and PROP phenotype. Subsequent searches included papers published before and after date of initial search (until May 2018). Results. Flavor preferences start as early as taste system development during pregnancy. Therefore, children who are exposed to sweet flavors in early childhood, increase their risk of habituation to them. Likewise, the hedonic experiences given by the ingestion of sweet foods and beverages, reinforce the consumption of these foods, perpetuating their selection in later stages. Preference for sweet taste has been associated with the development of obesity in children. Functional genetic variants related to taste perception can also contribute to the selection of certain types of foods and there is enough evidence that supports this idea. However, its contribution to a higher energy intake as well as a higher body weight has been poorly explored with inconsistent results. Conclusions. More evidence is required to understand the environmental and genetic interactions of taste perception, so in turn, it can be consider as a key factor for preventing child obesity.